Standard Precautions and Infection Control, Medical Students’ Knowledge and Behavior at a Saudi University: The Need for Change - Amin, Tarek Tawfik (Glob J Health Sci, 2013)
BACKGROUND: No previous studies have reported the knowledge of Saudi medical students about Standard Precautions (SPs) and infection control. OBJECTIVES: The objectives of this study were to assess medical students’ knowledge in clinical years at King Faisal University, Saudi Arabia about SPs’ and to explore their attitudes toward the current curricular/training in providing them with effective knowledge and necessary skills with regard to SPs. SUBJECTS AND METHODS: This cross sectional study targeted students in clinical stage at College of Medicine, King Faisal University, Saudi Arabia. A pre-tested anonymous self administered data collection form was used. Inquires about students’ characteristics, general concepts of infection control/SPs, hand hygiene, personal protective equipment, sharp injuries and disposal, and care of health providers were included. The main source of information for each domain was also inquired. The second part dedicated to explore the attitudes toward the curricular and teaching relevant to SPs. RESULTS: A total of 251 students were included. Knowledge scores in all domains were considerably low, 67 (26.7%) students scored ≥ 24 (out of 41points) which was considered as an acceptable level of knowledge, 22.2% in 4(th) year, 20.5% in 5(th) year and 36.8% in 6(th) year. Sharp injuries, personal protective equipment and health care of the providers showed the least knowledge scores. The main sources of knowledge were self learning, and informal bed side practices The majority of students’ believed that the current teaching and training are insufficient in providing them with the necessary knowledge and skills regarding SPs. CONCLUSION: The overall knowledge scores for SPs were low especially in the domains of hand hygiene, sharp management, and personal protective equipment reflecting insufficient and ineffective instructions received by medical students through the current curriculum posing them vulnerable to health facilities related infections. Proper curricular reform and training are required to protect students and their patients.